The Cinderella Complex on Psychology Students of Nusa Cendana University Kupang - Srikanditama, Maria Gracyas Renggu; Keraf, M. K. P. Abdi; Anakaka, Dian Lestari (Universitas Nusa Cendana, 2023)
Cinderella complex occurs because of the powerlessness in women caused by a lack of independence. Cinderella complex women who are in a relationship will do anything to their partner as long as they always together even though often experience violence both physically and verbally, women still do not want to be separated from their partner because they are very dependent on and need him and even consider as someone who will help her to live a better life. The aims of this study are to know tends and dominant factor of Cinderella complex at sixth semester of Psychology Study Program students, Public Health Faculty, Undana. It is a quantitative descriptive study. This study’s respondent are 123 students aged 20-23 years old. The results are students’ tendency to Cinderella complex is on medium level (89,43%), 21 years old and class A and C students tend to Cinderella complex is on high level. Self-infused submissiveness is the most dominant factor on Cinderella complex.